An act of treason : a sniper novel - Coughlin, Jack, 1966- (Coughlin, Jack, 1966- Sniper novel., 2011)
When their careers are thrown into turmoil by false charges of espionage, Marine sniper Kyle Swanson and CIA agent Lauren Carson turn to Kyle's mentor Jim Hall for help only to discover that he has gone rogue and is selling American secrets to a Middle East warlord.